Analysis of Non-Government Organizations Position in Filling Pre-Trial for the Purpose of Determining the Suspect - Setiawan, Peter Jeremiah; Fitriyana, Lolita; Negara, Puri Indah Sukma; Choirunnisa, Novia (Budapest International Research and Critics University, 2021)
AfterÂ Decision of the Constitutional Court Number 98 / PUU-X / 2012, NGO include third parties with an interest in submitting pre-trial proceedings by terminating investigations or terminating proceedings, but related to Post- Decision of Constitutional Court Number 21 / PUU-XII / 2014, it can be seen that there is an extension of pre-trial proceedings, one of which is the suspect's determination. It actually raises concerns about pre-trial object posed by NGO, whether or not it requires the determination of a suspect, it given that it is not written if it looks at grammatically. Based on background above, this research analyzes about first, can non-governmental organizations submit pre-trial applications for the purpose of determining a suspect? Secondly, what is the concern of juriesâ€™ respect to the position of Non-Governmental Organization that submitted a pre-trial application for the purpose of determining the suspect? This research is a normative legal research with an approach to laws, a philosophical approach and a case approach. Based on this research, it has been identified that First, NGO should first submit pre-trial applications for the purpose of assessing a suspect. Whereas, since Article 77(a), which is incidentally the subject-matter of pre-trial proceedings for NGO, has been extended, it should be interpreted that NGO also send pre-trial applications for the purpose of determining the suspect. Secondly, in some justices' reflections based on Constitutional Court's Decision Number: 98 / PUU-X / 2012 on May 21, 2013 jo. The justice considered, in Constitutional Court Decision Number 21/PUU-XII/2014, that the complainant as an NGO has a legal role in bringing a preliminary ruling against the object of suspectâ€™s determination.